Pemertahanan Bahasa Ibu Melalui Pendidikan Formal - Supriyanto Widodo (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
There are many language in Papua Province and Papua Barat Province that they use as mother languages as vernacular. Nowdays, part of the is dangerous of their live and may be come from their own language, may be come from extra language, their attitude of their own language is not positive and this is can increase speed to die.We can decrease their to die with many strategic steps, such as the language as a lesson on the school. But, this is not easy to do, because many constrains may be we meet, such as the teacher not available, and many devices that can use in the classroom is not ready.